1013 Cardiovascular Biomarkers and Pathophysiological Insights into Obstructive Sleep Apnea During Acute Coronary Syndrome. (27th May 2020) - Cheong, C S; Aung, A T; Chan, S; Lee, C
Abstract: Introduction: Obstructive sleep apnea (OSA) is prevalent and carries prognostic implication in patients with acute coronary syndrome (ACS). The relative contribution of pathophysiological mechanisms in ACS towards OSA is not well-studied. We examined the correlation between severity of OSA and myocardial necrosis, inflammation, wall stress, and fibrosis. Methods: A total of 89 patients admitted with ACS underwent an overnight sleep study during index admission. Plasma levels of peak troponin I, high-sensitivity C-reactive protein (hs-CRP), N-terminal pro-brain natriuretic peptide (NT-proBNP), and suppression of tumorigenicity 2 (ST2) were prospectively analyzed. Two patients diagnosed with central sleep apnea were excluded. Results: The recruited patients were divided into no (AHI <5 events/hour, 9.2%), mild (5-<15, 27.6%), moderate (15-<30, 21.8%), and severe (≥30, 41.4%) OSA. The respective Epworth Sleepiness Scale scores were 3.8±3.7, 5.3±4.9, 4.0±2.8, and 5.5±4.5 (p=0.734). Compared to the no, mild and moderate OSA groups, the severe OSA group had a higher body mass index (p=0.005). They were also more likely to present with ST-segment elevation ACS (vs non-ST-segment elevation ACS) (p=0.041), have undergone previous coronary artery bypass grafting (p=0.013), demonstrate complete coronary occlusion during baseline coronary angiography (p=0.049), and have a larger left atrium diameter measured on echocardiography (p=0.029). Likewise, the severe OSA group had higher plasma levels of troponin I (10584±13078, 11699±20130, 19280±30670, 37571±31269 µg/L; p=0.017), hs-CRP (8.1±9.2, 23.1±52.3, 9.3±17.1, 39.4±44.7 mg/L; p=0.004), and NT-proBNP (667±604, 765±856, 636±728, 1395±1220 pg/mL; p=0.004), but not ST2 (p=0.10). After adjusting for the effects of the confounding variables, severe OSA was independently associated with troponin I (i.e., myocardial necrosis; OR 1.00003, 95% CI 1.000013-1.000048; p=0.001) and NT-proBNP (i.e., myocardial wall stress; OR 1.00081, 95% CI 1.00021-1.00141; p=0.008). Conclusion: Severe OSA during the acute phase of ACS was associated with extensive myocardial necrosis and myocardial wall stress, but not with inflammation and myocardial fibrosis. Support: Nil